Discrimination and Workers' Expectations: Experimental Evidence - Antonio Filippin (Institute for the Study of Labor (IZA), 2003)
This paper is an experimental analysis of the role played by workers? expectations in explaining the puzzling long-run persistence of observed discrimination against certain minorities in the labor market. The experiment provides some evidence supporting the theoretical prediction that unequal outcomes may emerge due to disadvantaged workers? wrong expectations of being discriminated against. However, this effect is not long-lasting, since players learn the true state of nature in later stages of the experiment, failing to generate a Self-Confirming Equilibrium driven by wrong beliefs. The strategy method provides additional evidence that expectations matter.
Keywords: D84; J71; C92; J15; 330; experiments; discrimination; workers? expectations; Arbeitsmarktdiskriminierung; Ethnische Diskriminierung; Dynamisches Spiel; Unvollkommene Information; Arbeitsproduktivität; Erwartungstheorie; Experiment; Theorie